Delayed Respiratory Insufficiency and Extramuscular Abnormalities in Selenoprotein N-Related Myopathies - Shu Zhang (Frontiers Media S.A., 2021)
Background: Selenoprotein N-related myopathies (SEPN1-RMs) are a subset of congenital myopathies caused by mutations of Selenoprotein N gene (SELENON or SEPN1). Clinical phenotype is considered as highly consistent and little attention has been given to the extramuscular abnormalities.Methods: We reported clinical, histopathological, and genetic features of four Chinese patients with SEPN1-RM and performed literature review on delayed respiratory insufficiency and extramuscular involvement.Results: A total of four patients exhibited both the typical and atypical clinical features of SEPN1-RM. The classical manifestations included axial and limb girdle weakness, spinal rigidity, scoliosis, respiratory insufficiency, and multiminicore morphological lesions. However, high interindividual variability was noticed on disease severity, especially the onset of respiratory involvement. Two adult patients postponed respiratory insufficiency to the third decade of life, while two juvenile patients manifested early hypoventilation with puberty exacerbation. As atypical features, extramuscular involvement of weight gain, subcutaneous adipose tissue accumulation, intellectual disability, and mild cardiac changes were observed. Molecular findings revealed three novel mutations of SELENON such as c.1286_1288 del CCT, c.1078_1086dupGGCTACATA, and c.785 G>C. Ten cases with delayed respiratory insufficiency were identified from previous publications. A total of 18 studies described extramuscular abnormalities including joint contractures, alterations of body mass index (BMI), mild cardiac changes, and insulin resistance. Intellectual impairment was extremely rare.Conclusion: SEPN1-RM should be considered as a differential diagnosis in adult patients with delayed respiratory involvement. Extramuscular involvement such as body composition alterations deserves more clinical attention. The novel mutations of SELENON widened the genetic spectrum of patients with SEPN1-RM.